Circadian-like patterns in electrochemical skin conductance measured from home-based devices: a retrospective study - Vittrant, Benjamin; Courrier, Violaine; Yang, Rui-Yi; de Villèle, Paul; Tebeka, Samuel; Mauries, Sibylle; Geoffroy, Pierre A. (Frontiers in Neurology, 2023)
In this study, we investigated the potential of Electrical Skin Conductance (ESC) measurements gathered from home-based devices to detect circadian-like patterns. We analyzed data from 43,284 individuals, using Withings Body Comp or Body Scan scales, which provide ESC measurements. Our results highlighted a circadian pattern of ESC values across different age groups and countries. Our findings suggest that home-based ESC measurements could be used to evaluate circadian rhythm disorders associated with neuropathies and contribute to a better understanding of their pathophysiology. However, 1 further controlled studies are needed to confirm these results. This study highlights thus potential of digital health devices to generate new scientific and medical knowledge.